PENGARUH PERSONALITY TERHADAP SERVICE PERFORMANCE: PRAKTIK SUMBER DAYA MANUSIA DAN SERVICE CLIMATE SEBAGAI VARIABEL MODERATOR PADA PT MCDERMOTT INDONESIA - Sri Zuliarni; Reni Anjani (POLITEKNIK LP3I JAKARTA, 2026)
This research is motivated by observational data that shows very low service performance, causing problems with services in and out of vendors, vendors are companies that support raw materials and services needed by PTMcDermott Indonesia (PTMI) but there are often complaints from vendors because the services provided take a long time, there are several assessments that must be done in research, By conducting this research which aims to improve the service performance. The purpose of this study is to analyze the influence of personality on service performance, HR practices and service climate as moderator variables. This research was conducted at the QHSES Department in and out of PTMI as many as 104 respondents. The analytical techniques used in this study are descriptive analysis and SEM-PLS. Based on the results of personality analysis can influence service performance, HR practices and service climate can moderate the influence of personality on service perforformance. and HR paractics and service climate moderated significantly.